Optimization of the Polri Dikmas Lantas through School to Prevent Traffic Accident by Students in the Jurisdiction of the Sragen Police - Alvin Yehezkiel (Police Studies Review, 2022)
Traffic community education (Dikmas) is one very important factor to support / support Traffic Kamseltibcar. Dikmas Then uses it to knock on the hearts / invites the community to participate in creating the Traffic Security Committee. One of the activities of Dikmas Then is to provide counseling to all schools through the police to schools, both at the elementary, junior high, high school and even college levels. This is the background for the author to examine the Implementation of Traffic Dikmas at the Sragen Police to find out how it is implemented, the influencing factors and what efforts can optimize the Traffic Dikmas through Police Goes To School in the jurisdiction of the Sragen Police. The research approach used is qualitative where in writing it conducts research, collects, processes and analyzes research data. The data taken in the form of statements, opinions, ideas and also data. Based on interviews, observations and research data processing in the jurisdiction of the Sragen Police, it is stated that the quality of human resources is still lacking, budget is not accurate, standard operating procedures are not implemented and lack of support from infrastructure. Based on the results of key data research, the implementation of Traffic Education in the Sragen Police jurisdiction has not been maximized and the efforts to optimize Traffic Dikmas through the National Police by the Sragen Police Traffic Unit have not been maximized due to internal factors, namely human resources, budget, standard operating procedures and infrastructure as well as external factors that include the community. and geographical condition of Sragen Regency. For this reason, the Sragen Police Traffic Unit needs to optimize the Traffic Dikmas through the Goes To School Police.